The Undergraduate Psychology Practicum Program: Best Practices in Practicum Supervision - Lamzon, Gina R.; Alvarez, Margaret Helen U. (Silliman Journal, 2022)
This study looked into the undergraduate psychology practicum program as experienced by teachers handling the subject. Twelve practicum teacher-supervisors from major universities across the Philippines were interviewed using a qualitative phenomenological approach. Resulting data included their views and feelings about practicum supervision and the challenges and opportunities found in their work. Best practices were found associated with the practicum subject itself, the practicum teacher, the academic institution, partner agencies, and relevant government agencies and professional organizations.